Therapeutic effect of naringenin on ethanol-induced liver fibrosis in rats - Jayaraman, Jayachitra; Namsivayam, Nalini; Manivannan, Kavitha; Sundaresan, Uma (European Journal of Clinical and Experimental Medicine, 2025)
Introduction and aim. Liver fibrosis, a progressive disorder marked by the surplus buildup of extracellular matrix proteins, frequently results from long-term ethanol intake. Our aim of study is to investigate how naringenin’s antifibrotic properties impact ethanol induced liver fibrosis in rats. Material and methods. Rats were divided into four groups: groups 1 and 2 received carboxymethylcellulose (CMC) containing 0.5% glucose, while groups 3 and 4 received 20% ethanol (6 g/kg of body weight) over a 60-day period. In the last 30 days, naringenin (50 mg/kg) was administered each day to groups 2 and 4. Results. Rats treated with ethanol exhibited liver damage and fibrosis, leading to elevated serum concentrations of aspartate and alanine transaminases. Expression levels of matrix metalloproteinases (MMPs), tissue inhibitors of metalloproteinases (TIMPs), alpha-smooth muscle actin (α-SMA) and related proteins were compared with the control group. Conclusion. Ethanol-fed rats showed an increase in serum matrix metalloproteinases, TIMPs, α-SMA, transaminases, and other proteins compared to the control group. The administration of ethanol led to liver damage and fibrosis. During the final 30 days of the trial, the inclusion of naringenin in the diets of rats notably reduced the levels of α-SMA, MMP2, MMP9, TIMP1, along with serum levels of aspartate and alanine transaminase levels and significant differences were observed compared to control group.